Pediatric Rectal Prolapse - Rentea, Rebecca M.; St Peter, Shawn D. (Clinics in Colon and Rectal Surgery, 2018)
Rectal prolapse is a common and self-limiting condition in infancy and early childhood. Most cases respond to conservative management. Patients younger than 4 years with an associated condition have a better prognosis. Patients older than 4 years require surgery more often than younger children. Multiple operative and procedural approaches to rectal prolapse exist with variable recurrence rates and without a clearly superior operation. These include sclerotherapy, Thiersch's anal cerclage, Ekehorn's rectopexy, laparoscopic suture rectopexy, and posterior sagittal rectopexy.
Keywords: rectal prolapse; pediatric; sclerotherapy; surgery; rectopexy